Conflict minerals traceability – a fuzzy set analysis - Timmer, Stephane; Kaufmann, Lutz (International journal of physical distribution & logistics management, 2017)
Purpose The purpose of this paper is to investigate legal effects on social sustainability practices at buying firms. The US Dodd-Frank Act has forced listed companies to determine the degree to which their products contain conflict minerals (CM). The research question this study seeks to answer is the following: which factors influence a company’s ability to determine the provenance of its inputs? Design/methodology/approach The study examines secondary data in the form of CM reports of 50 US listed firms for two consecutive years using a fuzzy set qualitative comparative analysis (fsQCA) approach. Findings This study identifies different configurations of stakeholder salience and firm resources that lead individual companies to achieve high levels of traceability. Findings show that firms’ CM governance mechanisms are a key determinant in the firms’ capacity to meet regulatory traceability requirements. Further, the authors find that both the presence and absence of specific stakeholder pressures and firm resources can lead to traceability. Findings also suggest that firms can achieve traceability without any pressure from stakeholders. Research limitations/implications The study investigates the practices of individual firms that are subject to the Dodd-Frank Act, rather than adopting a supply chain-wide perspective. Further, proxies had to be used to measure several constructs because of reliance on firms’ reporting, which implies that the study did not account for certain behavioral factors that influence traceability. Practical implications This study provides managers of both resource-rich and less resource-rich firms with possible pathways for achieving CM traceability. Originality/value The study contributes to the field of sustainability by providing exploratory insights into the antecedents of traceability and deriving theoretical propositions to guide further research. The authors apply fsQCA to investigate secondary data over multiple years, thus using a novel configurational methodology.